Whether low-cost-carrier passengers spend more on duty-free goods at the airport? Evidence from Incheon International Airport. (July 2020) - Choi, Jong Hae; Park, Yonghwa; Wang, Kun; Xia, Wenyi
Abstract: With a dramatic growth in the low-cost carrier (LCC) traffic around the world, many airports have built budget terminals to accommodate the LCC flights with cheaper airport charge to the airlines but inferior shopping environment and service quality to the passengers. This study aims to answer the following research questions: i). Whether the LCC passengers have higher purchasing power than FSC (full-service carrier) passengers for the airport concessions, particularly the duty-free goods? ii). Would the budget terminal design contribute to or jeopardize the LCC passengers' airport concession expenditure? iii). How could the airport operator maximize its concession revenue by re-designing terminal or re-allocating flight slots? We collect the actual airport duty-free transaction data from Incheon International Airport (ICN) for an empirical investigation. Our empirical evidence first suggests that LCC passengers could have comparable or even higher purchasing power than FSC passengers in consuming duty-free goods at the airport. Among all the LCC passengers, Chinese have the highest purchasing power. Second, the inferior shopping environment and service quality of budget terminal seriously jeopardize the duty-free sales from the LCC passengers. Third, counterfactual analyses show that, if ICN could convert its budget terminal into a conventional terminal, 44 million USD more duty-free sales can be generated per year. Even keeping the current terminal design, re-allocating the LCC flights between the budget terminal and conventional terminal could bring approximately 4.9 million USD more duty-free sales per year. The findings provide managerial implications to ICN and other airports for effective airport revenue management. First, the budget terminal design may not be ideal to accommodate LCC traffic as it damages the concession revenue from particular LCC passengers with high purchasing power. Second, exploring the concession revenue from the growing LCC traffic could help maintain an airport's advantage in aeronautical charge under single-till regulation.